The influence of professional skepticism on fraud detection: the case of malaysian non-big 4 auditors / Sharifah Nazatul Faiza Syed Mustapha Nazri ... [et al.] - Syed Mustapha Nazri, Sharifah Nazatul Faiza; Zahba, Izzul Hazmi; Zolkaflil, Salwa; Zainuddin, Noriza (UiTM Press, 2023)
This study aimed to examine the relationship between an auditor's professional skepticism characteristics and fraud detection in Malaysia among the non - Big4 auditors, using the Hurtts' Professional Skepticism Framework. 200 questionnaires were collected from auditors who worked in non-Big 4 audit firms in Selangor and Kuala Lumpur. The analysis used in the study were Pearson correlation and multiple linear regression. Referring to the attribution theory as the underpinning theory, the findings of this study showed that there are significant relationships between questioning the mind, suspension judgement, interpersonal understanding, self-determining, and fraud detection. This study recommends that non-Big4 audit firms need to ensure that their auditors have the professional skepticism characteristic in performing the audit to enhance audit quality as well as increase fraud detection in Malaysia. The respondents consisted of only MIA members who worked as auditors in Selangor and Kuala Lumpur, Malaysia, resulting in a small sample size. Future research may extend the sample by including auditors from other states. This study is among the few which fills the gap of limited literature focussing on non-Big4 auditors in Malaysia, and the availability of reliable literature on the professional skepticism by Hurtt and on the detection of fraud issues, particularly in the Malaysian environment.